2021
DOI: 10.3390/s21124250
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Ultrasonic Range Improvements for an Assistive Device

Abstract: To achieve optimal mobility, visually impaired people have to deal with obstacle detection and avoidance challenges. Aside from the broadly adopted white cane, electronic aids have been developed. However, available electronic devices are not extensively used due to their complexity and price. As an effort to improve the existing ones, this work presents the design of a low-cost aid for blind people. A standard low-cost HC-SRF04 ultrasonic range is modified by adding phase modulation in the ultrasonic pulses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The results of calibration presented high correlations, the R² = 0.99 showed good precision the values, corresponding already observed to Abreu et al (2021), Therefore, the results calibrations showed values R² near the one with anothers sensors, whose calibrations were greater than 0.9 of the coefficients of determination (Sanches et al, 2020;2022b). Subsequently, a statistical analysis was performed using the obtained results, as shown in Table 5.…”
Section: Sensors In Parshall Flumes X Height Variationmentioning
confidence: 61%
“…The results of calibration presented high correlations, the R² = 0.99 showed good precision the values, corresponding already observed to Abreu et al (2021), Therefore, the results calibrations showed values R² near the one with anothers sensors, whose calibrations were greater than 0.9 of the coefficients of determination (Sanches et al, 2020;2022b). Subsequently, a statistical analysis was performed using the obtained results, as shown in Table 5.…”
Section: Sensors In Parshall Flumes X Height Variationmentioning
confidence: 61%
“…In hindsight, the placement of the sensors of the face, constantly shifting their projected angles meant that misreadings were highly probable. When tested in lab conditions, these proximity sensors are expected to perform reliably at differing trajectories [115], but when we inspect the sound recording and video footage, we observed many cases of unexpected readings during the performances in contrast to the testing phase. Participants would move closer together with no perceivable feedback.…”
Section: Technical Venerability Against Proxemic Awarenessmentioning
confidence: 95%
“…The range and accuracy benchmarks for the ultrasonic sensors are partially dependent on environmental variables such as ambient temperature and humidity. When working in typical indoor conditions, the ultrasonic sensors are expected to ensure a stable accuracy of up to 13 feet (4 metres), within a 15 • degree angle [115].…”
Section: Overview Of Componentsmentioning
confidence: 99%
“…In hindsight, the placement of the sensors of the face, constantly shifting their projected angles meant that misreadings were highly probable. When tested in lab conditions, these proximity sensors are expected to perform reliably at differing trajectories [116], but when we inspect the sound recording and video footage, we observed many cases of unexpected readings during the performances in contrast to the testing phase. Participants would move closer together with no perceivable feedback.…”
Section: Technical Venerability Against Proxemic Awarenessmentioning
confidence: 95%
“…The range and accuracy benchmarks for the ultrasonic sensors are partially dependent on environmental variables such as ambient temperature and humidity. When working in typical indoor conditions, the ultrasonic sensors are expected to ensure a stable accuracy of up to 13 feet (4 m), within a 15 degree angle [116].…”
Section: Overview Of Componentsmentioning
confidence: 99%